Pengaruh Konsumsi Buah Kurma Terhadap Peningkatan Kadar Hemoglobin Pada Ibu Hamil Trimester III - Sugita Sugita; Kuswati Kuswati (Jurnal Kebidanan dan Kesehatan Tradisional, 2020)
Background: Anemia in pregnant women is a condition of the mother with hemoglobin levels in her blood <11.0% gr. Prevention of anemia in pregnant women can be through various ways including the fulfillment of nutrients in the body obtained from fruits and vegetables, one of them by consumption of dates. Dates contain 1.02 mg of iron per 100 grams. This study aims to determine the effect of consumption of dates on the increase in hemoglobin levels in third trimester pregnant women in the Klateng Community Health Center. Method: This type of research is a quasy experiment with a non equivalent control group design pre-test-post test design. A population of 57 third trimester pregnant women The sampling technique used was purposive sampling, a sample of 30 respondents from third trimester pregnant women was obtained in the working area of ​​the Central Health Center in Klateng. The data analysis technique used is the Wilcoxon Sign Rank Test. Results: The average level of hemoglobin in the treatment group of hemoglobin levels pre (before) the administration of dates by 10.793 gr / dL and post (after) the administration of dates occurred an increase of 11,933 gr / dL and seen an increase (difference) from the average value of pre and post of 1,140 gr / dL with a standard deviation of 0.6643. Statistical test results obtained p value <0.05 (0.002 <0.05) so that Ho is rejected, Ha is accepted then consumption of dates has a statistically significant effect on increasing hemoglobin levels. Conclusion: From the results of these studies indicate the influence of consumption of dates to increase hemoglobin levels in third trimester pregnant women in the work area of ​​the Central Health Center.